The mechanism, electronic and ligand effects for reductive elimination from arylPd(ii) trifluoromethyl complexes: a systematic DFT study1. Issue 10 (14th March 2015) - Zhang, Song-Lin; Huang, Lu; Sun, Li-Jun
<x xml:space="preserve">Abstract</x> Detailed reaction mechanisms and ligand effects have been studied for reductive elimination of Ar–CF3 from Pd(ii) centers.